Invariants: real or nominal? - Baluta, Halyna (Actual Problems of Mind, 2017)
The author take notice of such a feature of symbol as repetitiveness what enables us to clarify the conditions and rules of its functioning and to find the key to some internal axiological orderings. The main claim of the paper is that some simplified and transformed by a social context cultural invariants do exist till now as repetitive elements of the life scenarios and communicative practices.